META ANALYSIS: APPLICATION OF THE KNISLEY MATHEMATICS LEARNING MODEL - Yuli Ismayanti; Syamsuri Syamsuri; Maman Fathurrohman; Anwar Mutaqin (LPPM Universitas Bina Bangsa, 2024)
This study aimed to conduct a meta-analysis of the application of Knisley's mathematical learning model and its impact on students' mathematics abilities. Research begins with formulating a research problem tracking the research results that are relevant for analysis. The data was collected by browsing the electronic journals through Google Scholar, a Garuda portal with the keywords